A legitimidade do ranqueamento da democracia brasileira elaborado pela Freedom House - Pereira, Leonardo dos Santos (2018)
The objective of this study is analyzing the legitimacy of the model of Brazilian democratic ranking elaborated by Freedom House in contrast to the historiography of the national representative system and popular participation in the political arena. Therefore, the scientific discourse of Freedom has been studied in its methodological variables and in its academic and political legitimacy, as a vehicle of private authority producing scientific discourse that establishes truth and power about the world democratic classification. The critical focus of the research rests on the Brazilian democratic model that, despite high international ranking, in the national factual panorama coexists with the low historical rates of electoral political participation. Freedom House's scientific discourse has been evaluated, and it is inferred that there are no methodological assumptions that cover the complexity of social formation, the peculiarities of the country's economic policy and cultural identity. Thus, there is an incongruity in the evaluation system, capable of assigning doubt to its legitimacy. The real political scenario in Brazil seems to have been emptied by the inability of governmentalism to contain, on one hand, the vertiginous increase in popular demands and, on the other, the predominance of interests outside of national, regional and social desires. So the study here summarized is predominantly qualitative and genealogical, building by the bibliographical and documentary retrieval of historical and contemporary facts, in order to help seeking the understanding of this problematic which hasn’t been overcome of the present moment in Brazil.